איך אתה פותח x ^ 2 / (x ^ 2-4) = x / (x + 2) -2 / (2 x)?

איך אתה פותח x ^ 2 / (x ^ 2-4) = x / (x + 2) -2 / (2 x)?
Anonim

תשובה:

אין פתרון

הסבר:

# x ^ 2 / (x ^ 2-4) = x / (x + 2) -2 / (2-x) # #

הופכת # x ^ 2 / (x ^ 2-4) = x / (x + 2) + 2 / (x-2) # #

בצד ימין, להכפיל ולחלק את החלק הראשון עם # x-2 #

בצד ימין, להכפיל ולחלק את החלק השני עם # x + 2 #

אנחנו מקבלים, הופכת # (x + 2) (x-2)) + (2 (x + 2)) (x-2) (x-2) (x + 2)) #

הופכת # x ^ 2 / (x ^ 2-4) = (x ^ 2-2x + 2x + 4) / (x ^ 2-4) # #

הופכת # x ^ 2 / (x ^ 2-4) = (x ^ 2 + 4) / (x ^ 2-4) # #

הופכת # x ^ 2 = (x ^ 2 + 4) #

אין פתרון